PENGGUNAAN KURIKULUM 2013 TERHADAP RANAH AFEKTIF ANAK SEKOLAH DASAR PADA MASA COVID-19 - Fenita Oktaviani Rachmat; Primanita Sholihah Rosmana; Sofyan Iskandar; Rufaidah Natasya Amalia; Nia Rosniati (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2022)
The 2013 curriculum is a curriculum that in its implementation emphasizes character education based on the character, understanding, and competence of students. The 2013 curriculum was used in distance learning during the COVID-19 pandemic while still emphasizing character education, namely in the affective realm. However, in practice, there are many obstacles and challenges such as indifferent students and students who are against educators and parents. This study uses descriptive qualitative data analysis techniques with literature studies by providing solutions and efforts to fulfill the affective domain of elementary school students when distance learning takes place. This manuscript contains the problems of distance learning, the effect of distance learning on the affective domain of elementary school students, and the solutions to these problems. This study uses a literature study by conducting an assessment of the results of research, articles, and case studies that have been carried out in the field.